Enhancing the GDEMs of Egypt Using a Surface Subtraction Approach - El-Ashmawy, Nagwa; Al-Krargy, Essam (Geomatics and Environmental Engineering, 2022)
This paper proposes an enhancement approach to improve the accuracy of global Digital Elevation Models (GDEMs) in Egypt. The proposed approach is an empirical one that depends on subtracting the heights error from the original DEM. The research includes the evaluation and enhancement of SRTM-1 (SRTM v4.1), ASTER GDEM v2, and AW3D30 v2 GDEMs, in Egypt, using 980 well distributed GPS/levelling points, that cover the entire country. The GPS/levelling points are divided into 500 control and 390 check points. The results show that the root mean square error (RMSE) in the SRTM, ASTER and AW3D30 are 3.99 m, 8.81 m, and 2.98 m respectively. For enhancing purposes, two different approaches are used: a linear regression analysis approach, and the proposed empirical surface subtraction approach. The results of the linear regression analysis approach show that the accuracies are improved by 3%, 16%, and 3% for SRTM, ASTER and AW3D30 respectively. However, the accuracies are improved by 5%, 23%, and 16% for SRTM, ASTER and AW3D30 respectively when the proposed approach is followed. After using the proposed approach, the obtained accuracy of the enhanced DEM reached 2.5 m.